The Tomb of Teungku Di Anjong: From History, Art Artifacts and Revitalization Motive for the Development of Aceh Creative Batik Design - Herwandi, Herwandi; Ibrahim, Husaini; Yusdi, Muhammad (Paramita: Historical Studies Journal, 2019)
Teungku Di Anjong is a great Ã¢â‚¬ËœpriesÃ¢â‚¬â„¢ who lived during his reign of Sultan Alaudin Mahmud Shah in the kingdom of Aceh Darussalam (1760 - 1781 AD). He is buried in Gampong Peulanggahan, Kutaraja Sub-district, Banda Aceh City. His tomb is in an old mosque complex, which the people named by the Teungku Di Anjong Mosque. The tomb of Teungku Di Anjong along with his wife's grave named Syarifah, which is in a construct (cungkub), has a jirat and two beautifully decorated tombstones. The decorations are generally in harmony with Islamic art, filled with Arabic flower and calligraphic ornaments. Teungku Di Anjong Tomb is an art artifact, an art product of the creative industry in the 18th century ago in Aceh, which is a continuation of the tradition of decorating the tomb from earlier times. This article will discuss the history of Teungku Di Anjong, in dynamics and its role in the development of history in the kingdom of Aceh Darussalam. Then, it will see the artifacts of the tomb of Tengku Di Anjong, which is associated with the revitalization of the ornament on the tomb, which can produce a new patented "motif" design that is registered to IPR (Intellectual Property Rights). The design of the new motif can be part of the enhancement of creativity for the development of batik motifs in Aceh Darussalam. Batik produced can have the character of Aceh and Islamic character.Ã‚Â Teungku Di Anjong adalah tokoh besar yang hidup pada masa pemerintahan Sultan Alaudin Mahmud Shah di kerajaan Aceh Darussalam (1760 - 1781 M). Ia dimakamkan di Gampong Peulanggahan, Kecamatan Kutaraja, Kota Banda Aceh. Makamnya berada di kompleks masjid tua, yang oleh orang-orang dinamai Masjid Teungku Di Anjong. Makam Teungku Di Anjong bersama dengan kuburan istrinya bernama Syarifah, memiliki jirat dan dua batu nisan yang didekorasi dengan indah. Dekorasi umumnya selaras dengan seni Islam, diisi dengan bunga Arab dan ornamen kaligrafi. Makam Teungku Di Anjong adalah artefak seni, produk seni dari industri kreatif pada abad ke-18 yang lalu di Aceh. Seni tersebut merupakan kelanjutan dari tradisi mendekorasi makam dari zaman sebelumnya. Artikel ini membahas sejarah Teungku Di Anjong, dalam dinamika dan perannya dalam pengembangan sejarah di kerajaan Aceh Darussalam. Kemudian, melihat artefak dari makam Tengku Di Anjong, yang terkait dengan revitalisasi ornamen di makam, yang dapat menghasilkan desain "motif" baru yang dipatenkan yang terdaftar pada HKI (Hak Kekayaan Intelektual). Desain motif baru dapat menjadi bagian dari peningkatan kreativitas untuk pengembangan motif batik di Aceh Darussalam. Batik yang dihasilkan dapat memiliki karakter Aceh dan karakter Islam.Ã‚Â